(untitled) (Simbiótica. Revista Eletrônica, 2026)
In this article we want to understand what political and institutional patterns emerge in countries that adopted semi-presidentialism after the third wave of democratization. In a cross-sectional research design and taking the country as our the unit of analysis, we identified 47 cases that were descriptively analyzed based on political and institutional characteristics, such as the degree of democratization, the subtype of semi-presidentialism, previous belonging to a semi-presidential country and the electoral system adopted for the lower house. Among the most relevant findings is that post-third wave semi-presidentialisms tend to be democracies, have premier-presidential arrangements, proportional electoral systems and former belonging to semipresidential countries.